The Islamization of the Jochid and Hulaguid Uluses in Comparison: Points of View from Muslim and Christian Sources - R. Hautala (Золотоордынское обозрение, 2018)
Research objectives: To consider and compare the processes of Islamization of nomads in the Hulaguid and Jochid uluses at the beginning of the rule of the Ilkhan Ghazan (1295–1304) and the Golden Horde’s Uzbek Khan (1313–1341). Research materials: Persian synchronous sources on the process of Islamization of the Ilkhanate’s nomads connected to the Ilkhan Ghazan’s ascension to power, significantly supplemented by the eyewitness report of the Sufi Sheikh Sadr al-Din Ibrahim b. Sa’d al-Din Hammuya, found in the work of al-Jazari. These are contrasted by the information found in local Armenian and Nestorian sources with the addition of more information provided by Latin authors. The comparison is made of traditional information from Persian and Mamluk chronicles with that found in synchronous Latin sources compiled within the Juchid ulus in light of the events in the Golden Horde and an assessment of the religious policy of Uzbek Khan. The novelty of this study is an attempt to compare the consequences of the ascensions of “Islamizing” khans in both uluses and in contraposition between the Muslim sources inclined to exaggerate successes regarding the Islamization of local nomads on one hand, and the information of Christian eyewitnesses to events on the other hand, allowing us to essentially diversify the notion of the religious policy both of Ilkhan Ghazan and the Golden Horde’s Uzbek Khan. As a result of a comparison of heterogeneous sources, the author comes to the conclusion that the rulers of both uluses were forced to adhere to the traditional policy of religious tolerance after they encountered the fierce resistance of nomads when they initially made moves to reverse it.